Subtle persistent working memory and selective attention deficits in women with premenstrual syndrome. (March 2017) - Slyepchenko, Anastasiya; Lokuge, Sonali; Nicholls, Brianne; Steiner, Meir; Hall, Geoffrey B.C.; Soares, Claudio N.; Frey, Benicio N.
Abstract: As a recurrent, cyclical phenomenon, premenstrual syndrome (PMS) affects a significant proportion of women of the reproductive age, and leads to regular monthly days of functional impairment. Symptoms of PMS include somatic and psychological symptoms, such as headaches, sleep disturbances, social withdrawal and mood changes, during the late luteal phase of the menstrual cycle, which alleviate during the follicular phase. This study investigated neurocognitive functioning in women with moderate to severe PMS symptoms ( n =13) compared to women with mild/no PMS ( n =27) through administration of a battery of neuropsychological tests during the asymptomatic follicular phase of the menstrual cycle. Relative to women with mild/no PMS symptoms, women with moderate to severe PMS showed significantly poorer accuracy and more errors of omission on the N-0-back, as well as more errors of omission on the N-2-back task, indicating the presence of impairment in selective attention and working memory. This study provides evidence of persistent, subtle working memory and selective attention difficulties in those with moderate to severe PMS during the follicular phase of the menstrual cycle. Highlights: Women with moderate to severe PMS had worse N-0-back and N-2-back task performance. These results suggest that impairment in selective attention and working memory. These cognitive impairments were present in the asymptomatic, follicular phase of the menstrual cycle.